Bilingualism in the primary school : a handbook for teachers - Mills, Richard W.; Mills, Jean, 1947- (Routledge, 2002)
Over the past few years bilingualism has come to be seen not as a hinderance to assimiliation but as an asset which, properly nurtured, will benefit children's linguistic awareness, cultural sensitivity and cognitive functioning. Bilingualism in the Primary Classroom gives primary teachers a window on the experience of the bilingual children in their care and by doing so helps them to make the most of what the children and their parents have to offer as well as giving them a good start in the National Curriculum. Many of the contributors to the book are themselves bilingual. -- Provided by publisher.